The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/microorganisms10050949
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Environment and Gut Microbiota: Lessons from Pet Dogs

Abstract: Accumulating data show the involvement of intestinal microbiota in the development and maintenance of numerous diseases. Many environmental factors influence the composition and function of the gut microbiota. An animal model subjected to the same environmental constraints that will allow better characterization of the microbiota–host dialogue is awaited. The domestic dog has physiological, dietary and pathological characteristics similar to those of humans and shares the domestic environment and lifestyle of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 122 publications
1
9
0
Order By: Relevance
“…1b). Overall, these bacterial abundances appear to be similar to those reported in other dogs, which suggests the existence of typical oral and gut microbiota in these animals (Ruparell et al 2020;Hernandez et al 2022).…”
Section: Oral and Gut Microbiota Analysed In This Studysupporting
confidence: 81%
“…1b). Overall, these bacterial abundances appear to be similar to those reported in other dogs, which suggests the existence of typical oral and gut microbiota in these animals (Ruparell et al 2020;Hernandez et al 2022).…”
Section: Oral and Gut Microbiota Analysed In This Studysupporting
confidence: 81%
“…While insights suggest that Inuit dogs have retained genetic markers unique to their indigenous history, these breeds have occupied overlapping geographical regions as sled dogs since the European colonization of the Arctic ( 109 , 110 ). Multiple studies have shown that gut microbial composition depends on environment ( 18 , 111 ), which may contribute to similarities in microbiota among dogs in this study. Careful longitudinal analysis of multiple samples from before and after intense activity and with and without glucosamine supplementation will likely provide further insights into the influence of these variables on microbiome composition.…”
Section: Discussionmentioning
confidence: 81%
“…Domestic dogs share the house with the owners. Its microbiota has a taxonomic similarity with humans, much larger than mice or pig (73,74). Living or working with another type of animals may in uence the human microbiota, too, due to their different speci c microbiota.…”
Section: Discussionmentioning
confidence: 99%